Brazilian unions face globalisation: learning to negotiate in regional blocs and global networks. (1st April 2008) - ,
Abstract : This paper discusses how Brazilians trade unions have been reacting to globalisation by analysing their participation in two different, though interrelated, initiatives. The first of these is the process of implementation of the Mercosul Southern Cone Common Market and the prominent role the unions played within it from its inception. The focus here is on how trade unions boosted the social agenda as a core issue in Mercosul's integration policy. The second initiative is the development of international company-based union networks which are now widespread in Brazil. What will be considered in both cases is the increasing importance of the actual practice of negotiation for the ongoing pattern of labour relations in Brazil, whether this is between state agencies and workers'' representatives, or between companies and their own workers. The paper points to the difficulties and opportunities for the union movement in each case.